2016
DOI: 10.1371/journal.pgen.1006308
|View full text |Cite
|
Sign up to set email alerts
|

MiR-155 Enhances Insulin Sensitivity by Coordinated Regulation of Multiple Genes in Mice

Abstract: miR-155 plays critical roles in numerous physiological and pathological processes, however, its function in the regulation of blood glucose homeostasis and insulin sensitivity and underlying mechanisms remain unknown. Here, we reveal that miR-155 levels are downregulated in serum from type 2 diabetes (T2D) patients, suggesting that miR-155 might be involved in blood glucose control and diabetes. Gain-of-function and loss-of-function studies in mice demonstrate that miR-155 has no effects on the pancreatic β-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 68 publications
6
71
0
Order By: Relevance
“…MiR-155 has a well-documented role in autoimmune and other chronic inflammatory diseases (28)(29)(30)(31). Furthermore, miR-155 has been demonstrated to regulate insulin sensitivity in vitro (32) and in vivo in mice (32,33). MiR-320 is currently considered as a potential target for type 2 diabetes mellitus therapy (34,35) since it regulates the expression of phosphoinositide-3-kinase (PI3K), a downstream mediator of insulin signaling.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-155 has a well-documented role in autoimmune and other chronic inflammatory diseases (28)(29)(30)(31). Furthermore, miR-155 has been demonstrated to regulate insulin sensitivity in vitro (32) and in vivo in mice (32,33). MiR-320 is currently considered as a potential target for type 2 diabetes mellitus therapy (34,35) since it regulates the expression of phosphoinositide-3-kinase (PI3K), a downstream mediator of insulin signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our results, as well as those of Gaudet et al (2016), suggest that miR155 deficiency in a male mouse model exposed to an HFD results in similar degree of impaired glucose metabolism and insulin resistance as WT HFD-fed mice. Lin et al (2016), however, found that miR155 deletion in male mice resulted in poorer glucose metabolism and greater insulin resistance than WT controls.…”
Section: Discussionmentioning
confidence: 95%
“…Lin et al. (), however, found that miR155 deletion in male mice resulted in poorer glucose metabolism and greater insulin resistance than WT controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations